Potential of Pramipexole in Attenuating Morphine Dependence: Insights from a Conditioned Place Preference Study in Mice - Shahzadi, Andleeb; Yunusoğlu, Oruç; Alhakim, Mohamad; Gökdemir, Selim; Ateşoğlu, Rüveyda Rümeysa (Cerrahpaşa Medical Journal, 2025)
Objective: Pramipexole, a selective dopamine D2/D3 receptor agonist, has been implicated in modulating dopaminergic transmission in brain reward circuits. Morphine reward-related behaviors are associated with a reduction in dopamine levels in these regions. This study aimed to investigate the effects of pramipexole on morphine dependence in a rodent model, based on the hypothesis that enhancing dopaminergic activity may attenuate opioid dependence. Method: Swiss albino mice with established morphine dependence were assessed using the conditioned place preference (CPP) test. Morphine conditioning was performed with 10 mg/kg morphine (IP) for 8 days. On the ninth day, animals received either 1 mg/kg or 4 mg/kg pramipexole (IP), and CPP expression was evaluated 30 minutes post-administration. Results: Pramipexole (1-4 mg/kg) significantly reduced morphine-induced CPP expression by 9%-14% (P < .05 to .01). No significant dose-dependent differences were observed, indicating a potential ceiling effect. Conclusion: These findings indicate that pramipexole, a dopamine D2/D3 receptor agonist, attenuates morphine dependence-related behaviors. Pramipexole may represent a potential pharmacotherapeutic candidate for opioid dependence, warranting further investigation in preclinical and clinical settings. Cite this article as: Shahzadi A, Yunusoğlu O, Alhakim M, Gökdemir S, Ateşoğlu RR. Potential of pramipexole in attenuating morphine dependence: Insights from a conditioned place preference study in mice. Cerrahpaşa Med J 2025, 49, 0020, doi: 10.5152/ cjm.2025.25020.